The “A's and H's” of Healthy and Unhealthy Relationships: Three Relationship Renewal Activities - Eckstein, Daniel G. (My University, 2004)
This article consists of three different activities that couples can complete together: Relationships are viewed contrasting the metaphor of the letter A with the letter H, eight healthy characteristics of couples by the Timberlawn Group are presented, and seven principles of marriage according to Gottman and Silver are included. Couples are invited to complete questions based on the concepts and discuss them with their partner. © 2004, Sage Publications. All rights reserved.
Keywords: couple's questionnaire; relationship renewal